Optimal Sharing of Labor Productivity Risks and Mix of Pay-As-You-Go and Savings - Debora Kusmerski Bilard (Tinbergen Institute, 2008)
The paper addresses two related issues: the optimal intergenerational sharing of laborproductivity risks, through a Pay-As-You-Go (PAYG) social security, and the mix ofPAYG and savings for retirement provision in a small open economy. It shows that partial contingency of the social security on the stochastic labor productivity is ex ante optimal,when the interest rate is above the expected growth rate of the economy and when thegovernment has a lifetime perspective of the risk exposure. The paper also provides acondition for partial displacement of savings by the PAYG, which is in line with vastempirical evidence.
Keywords: H55; H21; D91; 330; intergenerational risk sharing; PAYG social security; household's savings; Arbeitsproduktivität; Generationengerechtigkeit; Umlageverfahren; Sparen; Privater Haushalt; Kleine offene Volkswirtschaft; Theorie